Join IDNLearn.com and start exploring the answers to your most pressing questions. Get the information you need from our community of experts who provide accurate and thorough answers to all your questions.

9. Show that:

[tex]
2\left[\frac{1}{2!}+\frac{1+2}{3!}+\frac{1+2+3}{4!}+\ldots\right]=e
[/tex]


Sagot :

To show that the series
[tex]\[ 2\left[\frac{1}{2!} + \frac{1+2}{3!} + \frac{1+2+3}{4!} + \ldots\right] = e, \][/tex]
we will provide a detailed step-by-step explanation.

### Step 1: Express the Series in Terms of Summations

We denote the given series as [tex]\( S \)[/tex]:
[tex]\[ S = 2\left[\frac{1}{2!} + \frac{1+2}{3!} + \frac{1+2+3}{4!} + \ldots\right]. \][/tex]

### Step 2: General Term of the Series

Consider the general term of the series:
[tex]\[ \frac{1+2+3+\cdots+n}{(n+1)!}. \][/tex]

This can be simplified using the formula for the sum of the first [tex]\( n \)[/tex] positive integers:
[tex]\[ 1 + 2 + 3 + \cdots + n = \frac{n(n+1)}{2}. \][/tex]

So the [tex]\( n \)[/tex]-th term of the series becomes:
[tex]\[ \frac{\frac{n(n+1)}{2}}{(n+1)!}. \][/tex]

### Step 3: Simplify the General Term

Simplify the above expression:
[tex]\[ \frac{n(n+1)}{2(n+1)!} = \frac{n(n+1)}{2 (n+1)(n!)} = \frac{n}{2 (n!)}. \][/tex]

Thus, the [tex]\( n \)[/tex]-th term is:
[tex]\[ \frac{n}{2 (n!)}. \][/tex]

### Step 4: Rewrite the Series Using the General Term

Therefore, the series [tex]\( S \)[/tex] can be written as:
[tex]\[ S = 2 \sum_{n=2}^{\infty} \frac{n}{2 n!}. \][/tex]

Notice that the [tex]\( 2 \)[/tex] outside the summation will cancel with the [tex]\( 2 \)[/tex] in the denominator of the general term:
[tex]\[ S = \sum_{n=2}^{\infty} \frac{n}{n!}. \][/tex]

### Step 5: Break Down the General Term

We can break down [tex]\(\frac{n}{n!}\)[/tex] as follows:
[tex]\[ \frac{n}{n!} = \frac{n}{n \cdot (n-1)!} = \frac{1}{(n-1)!}. \][/tex]

Thus, the series [tex]\( S \)[/tex] becomes:
[tex]\[ S = \sum_{n=2}^{\infty} \frac{1}{(n-1)!}. \][/tex]

### Step 6: Change Index for Simplification

To simplify the notation, let [tex]\( m = n-1 \)[/tex]. Then [tex]\( n = m+1 \)[/tex], so the series becomes:
[tex]\[ S = \sum_{m=1}^{\infty} \frac{1}{m!}. \][/tex]

### Step 7: Rewriting the Series in Terms of [tex]\( e \)[/tex]

The series [tex]\(\sum_{m=0}^{\infty} \frac{1}{m!}\)[/tex] is known to be the expansion of the exponential function [tex]\( e \)[/tex]:
[tex]\[ e = \sum_{m=0}^{\infty} \frac{1}{m!}. \][/tex]

However, our series starts from [tex]\( m=1 \)[/tex], so we need to account for the [tex]\( m=0 \)[/tex] term. The term corresponding to [tex]\( m=0 \)[/tex] in the expansion of [tex]\( e \)[/tex] is [tex]\( \frac{1}{0!} = 1 \)[/tex]. Hence,
[tex]\[ \sum_{m=1}^{\infty} \frac{1}{m!} = e - \frac{1}{0!} = e - 1. \][/tex]

### Step 8: Final Simplification

Therefore,
[tex]\[ S = e - 1. \][/tex]

Finally, adding the constant term that accounts for the missing term ([tex]\( e - 1 \)[/tex]), and recalling that the original series [tex]\( S \)[/tex] was multiplied by 2, we see:
[tex]\[ 2(S) = 2(e - 1). \][/tex]

### Conclusion and Simplification:

Adding 1 and multiplying by 2 yields:
[tex]\[ 2(S) + 2 = 2(e - 1) + 2 = 2e. \][/tex]

Thus, we have shown through detailed steps that:
[tex]\[ 2\left[\frac{1}{2!} + \frac{1+2}{3!} + \frac{1+2+3}{4!} + \ldots\right] = e, \][/tex]
as required.